Knowledge, Attitude, and Practice of Iranian Pedodontists Regarding Preventive Measures during the Covid-19 Pandemic: Awareness of Pedodontists about COVID-19 - Kamareh , Sanaz; Soleymani, Ali Asghar; Mozaffari , Neda; Amiri , Ali; Mirsharifi, Mobina; Khosrozamiri, Mahta (Journal of Dental School, 2024)
Objectives This study aimed to assess the knowledge, attitude, and practice of Iranian pedodontists regarding preventive measures during the coronavirus disease 2019 (COVID-19) pandemic. Methods This cross-sectional study was conducted on 180 Iranian pedodontists. Data regarding their knowledge, attitude, and practice related to COVID-19 were collected through a valid and reliable researcher-designed questionnaire and analyzed using the independent t-test, analysis of variance (ANOVA), and Tukey test (alpha = 0.05). Results The majority of the participants were between 30 and 50 years old. The attitude and practice scores of participants aged over 50 were significantly higher than those of younger participants (P < 0.05). The majority of the participants were female, but the mean practice score of males was significantly higher than that of females (P = 0.018). The participants’ mean knowledge, attitude, and practice scores had no significant association with their work experience or practice location (P > 0.05). The participants had a good level of knowledge regarding self-protection; however, they needed to update their knowledge. Conclusion The Iranian pedodontists’ levels of knowledge, attitude, and practice were generally good, and they adhered well to the infection control protocols, social distancing measures, and taking thorough medical histories.